Mary - “Cathedral of silence” in the view of Pope Francis - Wojtczak, Adam (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
Pope Francis gave Mary the distinctive title of “Cathedral of silence” and confesses that it is a beautiful image that teaches us the art of living with God. Although he does not explore directly and comprehensively its theological significance, in many statements he returns to the motif of Mary’s silence. It is therefore interesting and useful to follow in the footsteps of papal statements in order to discover the basic content of this Marian title and at the same time point out the originality of Francis’s interpretation. The article consists of three points. The first indicates that God is the God of surprises. He seeks to hide the mystery of His actions. Mary experienced this when She was amazed to discover that it was God who endowed Her with the fullness of grace and called Her to become the Mother to the Son of God. In the silence of Her heart, She accepted the will of God. She later turned out to become - the second point - the silent Socia Christi, who not only carried the Son in Her womb and gave birth to Him, but also accompanied Him from the Annunciation to Calvary. In silence and adoration, she put Him in the centre of attention without taking His place. In this way - the third point - She became for us an icon of a quiet and humble relationship with God. She proves that the beauty of Christian life is born not from speaking, but from silent communing with the mystery of God.